2017
DOI: 10.1002/ece3.3178
|View full text |Cite
|
Sign up to set email alerts
|

Honey bee‐collected pollen in agro‐ecosystems reveals diet diversity, diet quality, and pesticide exposure

Abstract: European honey bees Apis mellifera are important commercial pollinators that have suffered greater than normal overwintering losses since 2007 in North America and Europe. Contributing factors likely include a combination of parasites, pesticides, and poor nutrition. We examined diet diversity, diet nutritional quality, and pesticides in honey bee‐collected pollen from commercial colonies in the Canadian Maritime Provinces in spring and summer 2011. We sampled pollen collected by honey bees at colonies in four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 67 publications
7
44
1
2
Order By: Relevance
“…Even without being able to communicate resource locations, honey bee colonies seemed to exploit a variety of available resources. This is in line with earlier studies on effects of landscapes on diversity of honey bee pollen diets which found no effect of local resource diversity on diversity of foraged pollen in temperate landscapes (Colwell et al, ; Danner et al, ). In low‐diversity environments a diverse pollen diet could be maintained by increasing foraging ranges (Danner et al, ) and increasing the scouting activity if few pollen sources are advertised (Beekman, Gilchrist, Duncan, & Sumpter, ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Even without being able to communicate resource locations, honey bee colonies seemed to exploit a variety of available resources. This is in line with earlier studies on effects of landscapes on diversity of honey bee pollen diets which found no effect of local resource diversity on diversity of foraged pollen in temperate landscapes (Colwell et al, ; Danner et al, ). In low‐diversity environments a diverse pollen diet could be maintained by increasing foraging ranges (Danner et al, ) and increasing the scouting activity if few pollen sources are advertised (Beekman, Gilchrist, Duncan, & Sumpter, ).…”
Section: Discussionsupporting
confidence: 91%
“…Remarkably, this seems not to be true for honey bees in temperate landscapes. In field studies, local and landscape level flower richness had little effect on the diversity of pollen harvest in honey bees (Colwell, Williams, Evans, & Shutler, ; Danner, Keller, Härtel, & Steffan‐Dewenter, ) and even in the presence of mass‐flowering crops, honey bees were more likely to forage on alternative resources (Garbuzov, Couvillon, Schürch, & Ratnieks, ; Holzschuh et al, ). In fact, honey bees actively recruit nest mates to distant, but diverse semi‐natural resource patches, even when mass‐flowering crops in the vicinity of hives are available (Danner et al, ; Danner, Molitor, Schiele, Härtel, & Steffan‐Dewenter, ).…”
Section: Introductionmentioning
confidence: 99%
“…There are spring specialists whose diets fall outside that of social bees (e.g., Geranium, Andrena distans, Wood and Roberts, 2018), but they are in the minority, and the overall proportion of specialists is low due to the large numbers of generalist polylectic species flying at this time. Consequently, the extensive pollen collection from native North American trees and shrubs in the spring by honey bees (Adams et al, 1978;Olsen et al, 1979;Severson and Parry, 1981;Girard et al, 2012;Colwell et al, 2017) is seen also in the native social bee community.…”
Section: Discussionmentioning
confidence: 99%
“…In the Midwest, honey bees have been recorded gathering large quantities of pollen from non-native plant species during the summer period between late June and September (Adams et al, 1978;Olsen et al, 1979;Severson and Parry, 1981;Sponsler and Johnson, 2015;Long and Krupke, 2016;Smart et al, 2016Smart et al, , 2017. The extensive use of nonnative pollen during the summer contrasts with honey bee pollen use during the Midwestern spring, where colonies instead forage widely from native trees and shrubs (Adams et al, 1978;Olsen et al, 1979;Severson and Parry, 1981;Girard et al, 2012;Colwell et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…De fato, o uso de pesticidas, para além da contaminação de agricultores e a população em geral, pode promover perturbações nas populações de outros organismos no próprio agroecossistema, ou nos ecossistemas adjacentes aos locais de aplicação de pesticidas. Um exemplo prático dos efeitos dos pesticidas para organismos não humanos, é o uso inseticidas, que podem atingir organismos não-alvo, como as espécies de organismos polinizadores, causando a contaminação, morte e declínio de suas populações, e assim, a exclusão de seus serviços ecossistêmicos (COLWELL et al, 2017;MCART et al 2017).…”
Section: A Biodiversidade E O Movimento Estudantil Da Biologiaunclassified